Fruit extracts from Phyllanthus emblica accentuate cadmium tolerance and accumulation in Platycladus orientalis: A new natural chelate for phytoextraction. (1st July 2021) - Guo, Bin; Liu, Chen; Lin, Yicheng; Li, Hua; Li, Ningyu; Liu, Junli; Fu, Qinglin; Tong, Wenbin; Yu, Haiping
Abstract: A key challenge for phytoextraction is the identification of high efficiency, growth-supporting, and low cost chelating agents. To date, no substance has satisfied all above criteria. This study investigated nine traditional Chinese herbs and found that Phyllanthus emblica fruit (FPE) extract could be utilised as an optimal chelate for the phytoextraction of cadmium (Cd)-contaminated soils. FPE application into soil at a ratio of 0.1% (w/w) significantly increased extractable Cd (by 43%) compared to the control. The success of FPE as a chelating agent was attributed to high quantities of polyphenol compounds (0.76%) and organic acids (9.6%), in particular, gallic acid (7.6%). Furthermore, antioxidative properties (1.4%) and free amino acids in FPE alleviated Cd-induced oxidant toxicity and enhanced plant biomass. FPE promoted 78% higher phytoextraction efficiency in Platycladus orientalis compared to traditional chelating agents (EDTA). Furthermore, 76% of FPE was degraded 90 days after the initial application, and there was no difference in extractable Cd between the treatment and control. FPE has been commercially produced at a lower market price than other biodegradable chelates. As a commercially available and cost-effective chelator, FPE could be utilised to treat Cd-contaminated soils without adverse environmental impacts. Graphical abstract: Image 1 Highlights: Fruit extract from Phyllanthus emblica (FPE) is found to be an effective Cd chelator. FPE comprised high phenolic compounds, especially for gallic acid. FPE promoted plant tolerance, growth and Cd phytoextraction. FPE presented high efficiency, low risk and cost effective compared with EDTA. FPE can help remediate contaminated soils with no adverse environmental impact.